Potenciando la Inclusión Educativa: El Impacto Transformador de la Tecnología en el Aprendizaje de Adolescentes con Discapacidad Visual (Memorias Sifored - Encuentros Educación UAN, 2023)
This research investigates the strategies and contributions that have been made through the emergence of ICTs to be implemented in the educational field focused on adolescents with visual impairment. This is done through articles that provide information on the strategies implemented so that adolescents can create, share and access learning without being excluded and rejected, taking into account that technology has revolutionized considerably, therefore, research is conducted on inclusive education as it is a process aimed at ensuring the right to quality education for all students on equal terms, paying special attention to those who are most excluded, with the purpose of ensuring equal opportunities for all.
Keywords: educational inclusion; Visual impairment; Impact of technology; adolescents; learning